American studies today: new research agendas - Fluck, Winfried (Winter, 2014)
The volume explores the state of contemporary American Studies in the light of recent developments and currently emerging perspectives of research. Featuring contributions by leading American Studies scholars from the German-speaking world, the collection of essays represents a broad spectrum of thematic, theoretical and methodological approaches that constitute major research agendas within current American Studies. It also includes contributions by renowned colleagues from the U.S. which provide a transatlantic framework of scholarly debate. In line with the original, dialogic conference for
Description based upon print version of record
Keywords: Electronic books